48 Trends in the incidence and outcome of paediatric out-of-hospital cardiac arrest in victoria, australia. (16th April 2018) - Nehme, Z; Namachivayam, S; Butt, W; Bernard, S; Smith, K
Abstract : Aim: System-based improvements to the chain of survival have yielded significant increases in survival from out-of-hospital cardiac arrest (OHCA) in adults. Comparatively little is known about the long-term trends in incidence and survival following paediatric OHCA. Method: Between 2000 and 2016, we included paediatrics aged ≤16 years who suffered a non-traumatic OHCA in the state of Victoria, Australia. Trends in incidence and unadjusted outcomes were assessed using linear regression. Adjusted trends in event survival and survival to hospital discharge were assessed using multivariable logistic regression. Results: Of the 1301 paediatric OHCA attended by emergency medical services (EMS), 948 (72.9%) received an attempted resuscitation. The overall incidence of EMS-attended OHCA was 6.7 cases per 1 00 000 person-years, with no significant change over time. Although median EMS response times increased over time, the proportion of cases with OHCA identified in the call and receiving bystander cardiopulmonary resuscitation (CPR) also increased. Unadjusted event survival rose from 23.3% in 2000 to 33.3% in 2016 (p trend=0.007). Over the same period, survival to hospital discharge rose from 9.4% to 17.7% (p trend=0.04). After multivariable adjustment, the odds of event survival and survival to hospital discharge increased independently of arrest factors, by 7% (OR 1.07, 95% CI: 1.03, 1.12; p=0.001) and 8% (OR 1.08, 95% CI: 1.01, 1.15; p=0.02) respectively. Bystander CPR and OHCA identification in the call were not associated with survival. Conclusion: In our region, survival following paediatric OHCA increased significantly over a 17 year period. However, the factors contributing to this improvement require further investigation. Conflict of interest: None Funding: ZN is funded by a National Health and Medical Research Council (NHMRC) Early Career Fellowship (#1146809).